Winter Aconite (Eranthis hyemalis) Lectin as a cytotoxic effector in the lifecycle of Caenorhabditis elegans - Marie-Therese McConnell; David R. Lisgarten; Lee J. Byrne; Simon C. Harvey; Emilia Bertolo (PeerJ, 2015)
The lectin found in the tubers of the Winter Aconite (Eranthis hyemalis) plant is an N-acetyl-D-galactosamine specific Type II Ribosome Inactivating Protein (RIP); Type II RIPs have shown anti-cancer properties, and hence have potential as therapeutic agents. Here we present a modified protocol for the extraction and purification of the E. hyemalis lectin (EHL) using affinity chromatography. De novo amino acid sequencing of EHL confirms its classification as a Type II Ribosome Inactivating Protein. The biocidal properties of EHL have been investigated against the nematode Caenorhabditis elegans. Arrested first stage larvae treated with EHL have shown some direct mortality, with surviving larvae subsequently showing a range of phenotypes including food avoidance, reduced fecundity, developmental delay and constitutive dauer larvae formation. Both inappropriate dauer larvae development and failure to locate to bacterial food source are consistent with the disruption of chemosensory function and the ablation of amphid neurons. Further investigation indicates that mutations that disrupt normal amphid formation can block the EHL-induced dauer larvae formation. In combination, these phenotypes indicate that EHL is cytotoxic and suggest a cell specific activity against the amphid neurons of C. elegans.